Effects of Parecoxib Sodium Application Combined with Enhanced Recovery After Surgery Nursing on Inflammatory Factors and Knee Joint Function in Elderly Patients After Total Knee Arthroplasty - Deng, Liqiong; Tan, Liping (Frontiers in Surgery, 2022)
Objectives To study the effect of parecoxib sodium (PS) application, combined with enhanced recovery after surgery (ERAS) nursing, on inflammation and knee joint function in elderly patients after total knee arthroplasty (TKA). Methods In this prospective cross-sectional study, we recruited 120 elderly patients treated with TKA who were randomly divided into two groups, the combine group and the control group, with 60 patients in each group. Patients in the control group received ERAS nursing and normal saline, and the patients in the combine group received ERAS nursing and PS. At different times after surgery, we compared the hemoglobin (Hb), complete white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and serum IL-1β, TNF-α, and IL-6, and recovery time for different ranges of joint motion and the knee joint function HSS (hospital for special surgery scale) score between the two groups. Results On the third and seventh postoperative days, the levels of Hb in the patients of the combine group were significantly lower than those in the control group (p < 0.05), while the levels of WBC, ESR, serum IL-1β, TNF-α, and IL-6 in the patients of the combine group were all significantly lower than those in the control group (p < 0.05). Compared with the patients in the control group, the recovery time for 30, 60, 90, and 120 angles of joint motion in patients of the combine group was significantly decreased (p < 0.05), and the HSS score of patients in the combine group was significantly higher than that in the control group on the first, third, and sixth postoperative months (p < 0.05). Conclusion Elderly TKA patients who received PS application, combined with ERAS nursing, had lower inflammation in peripheral blood 2 weeks after operation and faster postoperative recovery of knee joint function.